Improving Employee Performance: The Role Of OCB Between Personal Trust And Leadership - Ampauleng; Salma Abdullah (Jurnal Manajemen, 2022)
The purpose of this study is to investigate the improvement of employee performance with the role of OCB in mediating the relationship of personal trust and leadership. The sampling method illustrated in this research uses a purposive sampling method, namely the Makassar Main Kesyahbandaran Office employees who have extra motivation as many as 54 people. The analytical tool used is WarpPLS 7. 0. Personal trust has a positive and significant impact on employee performance. After that, leadership does not significantly affect employee performance. Next, personal trust has a positive and meaningful influence on OCB. Then, leadership has a positive and significant influence on OCB. Likewise, OCB has a positive and significant impact on employee performance. After that, personal beliefs have a positive and significant impact on employee performance through OCB. And finally, leadership has a positive and significant impact on employee performance through OCB. The originality of this research applies the principle of "SYAHDU" as the basis for employee performance.